Ordinance of May 25, 1914, §§4a-6. (Samuel A. Ettelson, Opinions of the Corporation Counsel and Assistants from May 1, 1915, to June 30, 1916, at 458-59 (Vol. 7, 1916) - (:unkn) unknown (General Publisher, 1914)
Required weapon sales through licensed dealers only; required purchasers of such weapons to first receive a permit from the General Superintendent of Police. Required purchasers provide proof of good moral character to receive permit; gives Superintendent discretion on issuance of permits. Prohibited the issuance of permits to anyone who was convicted of any crime and minors. Punishable by a fine.
--
Keywords: TRANSFER & POSSESSION